1967
DOI: 10.1146/annurev.bi.36.070167.002413
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Viral DNA Molecules

Abstract: Without known exception, purifi ed virus particles, the virions, contain a single type of nucleic acid-RNA or DNA-never both. This fact provides the most convenient definition of a virus particle (115). The distinction be tween RNA-containing and DNA-containing viruses appears to be a pro found one that reflects a fundamental difference in their life cycle and evo lutionary origin. This review will be concerned with the DNA-containing viruses.It is generally a greed that viruses are reproduced from their own n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…Unbroken DNA molecules were extracted by rolling equal volumes of purified phage suspension and freshly distilled water-saturated phenol on a test-tube roller with the tubes rotating about their long axis at 75 rev./min. The details of this method were described by MacHattie et al (1967). The extracted DNA was dialysed 4 to 5 times against a large excess of 0"05 M-NaC1, o.o~ M-tris, pH 8"0 to remove residual phenol and stored at 4 ° .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unbroken DNA molecules were extracted by rolling equal volumes of purified phage suspension and freshly distilled water-saturated phenol on a test-tube roller with the tubes rotating about their long axis at 75 rev./min. The details of this method were described by MacHattie et al (1967). The extracted DNA was dialysed 4 to 5 times against a large excess of 0"05 M-NaC1, o.o~ M-tris, pH 8"0 to remove residual phenol and stored at 4 ° .…”
Section: Methodsmentioning
confidence: 99%
“…These phages were chosen because their DNA molecules, like those of T5, have non-permuted base sequences (Olligs, 1967;Thomas & MacHattie, 1967). It has been suggested that the maturation of phage DNA molecules in some cases involves the excision of phage-equivalent lengths of DNA from larger DNA structures known as concatemers (Streisinger, Emrich & Stahl, I967;Thomas, Kelly & Rhoades, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The packaging mechanism cuts the DNA when the head is filled, and it appears that EndoVII trims branches of DNA even after packaging has been initiated (523). The head full of DNA is about 3% longer than the genome size, accounting for the circular permutation of T4 genomes, with terminal redundancy of each genome; this circular permutation is the basis for the circular T4 genetic map (1048,1049,1073). Shorter or longer phage heads are occasionally formed, due to assembly errors that are increased by specific mutations in some head genes (256) or by incorporation of arginine analogues (194).…”
Section: Dna Packagingmentioning
confidence: 99%
“…Hoechst 33258 was obtained from Molecular Probes, Inc., Eugene, OR. T7 DNA was employed because it is a long linear dsDNA of known size (37,900 bp; molecular weight 25 × 10 6 daltons) devoid of single-chain interruptions [16]. 90CE was synthesized as previously described [17].…”
Section: Chemicalsmentioning
confidence: 99%